Single-Cell Transcriptome Profiling Unravels Distinct Peripheral Blood Immune Cell Signatures of RRMS and MOG Antibody-Associated Disease - Liu, Ju; Yang, Xiaoyan; Pan, Jiali; Wei, Zhihua; Liu, Peidong; Chen, Min; Liu, Hongbo (Frontiers in Neurology, 2022)
Relapsing-remitting multiple sclerosis (RRMS) and myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) are inflammatory demyelinating diseases of the central nervous system. Due to the shared clinical manifestations, detection of disease-specific serum antibody of the two diseases is currently considered as gold standard for the diagnosis; however, the serum antibody levels are unpredictable during different stages of the two diseases. Herein, peripheral blood single-cell transcriptome was used to unveil distinct immune cell signatures of the two diseases, with the aim to provide a predictive discrimination. Single-cell RNA sequencing was conducted on the peripheral blood from three subjects, including one patient with RRMS, one patient with MOGAD, and one healthy control. The results showed that the CD19+ CXCR4+ naive B cell subsets were significantly expanded in both RRMS and MOGAD, which was verified by flow cytometry. More importantly, RRMS single-cell transcriptomic was characterized by increased naive CD8+ T cells and cytotoxic memory-like NK cells, together with decreased inflammatory monocytes, whereas MOGAD exhibited increased inflammatory monocytes and cytotoxic CD8 effector T cells, coupled with decreased plasma cells and memory B cells. Collectively, our findings indicate that the two diseases exhibit distinct immune cell signatures, which allows for a highly predictive discrimination of the two diseases and paves a novel avenue for diagnosis and therapy of neuroinflammatory diseases.